Relationship of coffee consumption with a decline in kidney function among patients with type 2 diabetes: The Fukuoka Diabetes Registry. Issue 6 (22nd February 2022) - Komorita, Yuji; Ohkuma, Toshiaki; Iwase, Masanori; Fujii, Hiroki; Ide, Hitoshi; Oku, Yutaro; Higashi, Taiki; Oshiro, Ayaka; Sakamoto, Wakako; Yoshinari, Masahito; Nakamura, Udai; Kitazono, Takanari
Abstract: Aims/Introduction: The evidence regarding the effects of coffee consumption on incident chronic kidney disease is inconclusive, and no studies have investigated the relationship in patients with diabetes. We aimed to prospectively investigate the relationship between coffee consumption and the decline in estimated glomerular function rate (eGFR) in patients with type 2 diabetes. Materials and Methods: A total of 3, 805 patients (2, 112 men, 1, 693 women) with type 2 diabetes (mean age 64.2 years) and eGFR ≥60 mL/min/1.73 m 2 were followed (completion of follow up, 97.6%; median 5.3 years). Coffee consumption was assessed at baseline. The end‐point was a decline in eGFR to <60 mL/min/1.73 m 2 during the follow‐up period. Results: During follow up, 840 participants experienced a decline in eGFR to <60 mL/min/1.73 m 2 . Higher coffee consumption reduced the risk of decline in eGFR. Compared with no coffee consumption, the multivariate‐adjusted hazard ratios (95% confidence intervals) were 0.77 (0.63–0.93) for less than one cup per day, 0.77 (0.62–0.95) for one cup per day and 0.75 (0.62–0.91) for two or more cups per day ( P for trend 0.01). This trend was unaffected by further adjustment for baseline eGFR and albuminuria. The mean eGFR change per year was −2.16 mL/min/1.73 m 2 with no coffee consumption, −1.89 mL/min/1.73 m 2 with less than one cup per day, −1.80 mL/min/1.73 m 2 with one cup per day and −1.78 mL/min/1.73 m 2 with two or more cups per day ( P for trend 0.03). Conclusions: Coffee consumption is significantly associated with a lower risk of decline in eGFR in patients with type 2 diabetes. Abstract : Higher coffee consumption was significantly associated with reduced risk of chronic kidney disease development in patients with type 2 diabetes. The protective effect of coffee consumption on chronic kidney disease was stronger in subgroups of patients with poor glycemic control and longer diabetes duration.